Expansion of Avars and Slavs in the areas of Roman province of Dalmatia - Imamović, Mersiha; Omerčević, Bego (Historical Thought, 2025)
In the second half of the VI century there has been intensified expansion of Slavs and Avars in the areas of the former Roman Empire, and thus in the regions of the Roman province of Dalmatia. They were unscrupulously killing and looting the existing population and destroying their material goods of every kind on a mass scale. The expansion of Avars and Slavs marked the beginning of the destruction and complete suppression of all the achievements of ancient culture and civilization. Both first came to the regions of the Roman province of Pannonia, and then, a little later, on the areas of the province of Dalmatia. The Avar conquest of Sirmium, a strategically important town in Pannonia, opened the path to joint Avar-Slavic tribes for their breakthrough into the areas of Roman province of Dalmatia. During their expansion many cities on the territory of present-day Bosnia and Herzegovina, on the present-day Croatian coastal area and in part of present-day western Serbia, have been destroyed. With conquering of Salona, the capital of the province of Dalmatia, Avars and Slavs have achieved their ultimate goal.